Reversible feedback confinement. (18th October 2016) - Granger, Léo; Dinis, Luis; Horowitz, Jordan M.; Parrondo, Juan M. R.
Abstract: We present a feedback protocol that is able to confine a system to a single micro-state without heat dissipation. The protocol adjusts the Hamiltonian of the system in such a way that the Bayesian posterior distribution after measurement is in equilibrium. As a result, the whole process satisfies feedback reversibility —the process is indistinguishable from its time reversal— and assures the lowest possible dissipation for confinement. In spite of the whole process being reversible it can surprisingly be implemented in finite time. We illustrate the idea with a Brownian particle in a harmonic trap with increasing stiffness and present a general theory of reversible feedback confinement for systems with discrete states.